Measurement of ductions and fields of binocular single vision (BSV): orthoptic practice in the UK and Ireland. (3rd April 2021) - Jukes, Catherine; Bjerre, A.; Codina, C.; Griffiths, H.
ABSTRACT: To evaluate the current clinical practice of quantifying ductions and fields of BSV in the UK and Ireland using an online questionnaire. An anonymous online questionnaire with twenty–one questions was distributed in February 2019 via the British and Irish Orthoptic Society (BIOS) members' newsletter. Objectives were to investigate: methods used, frequency of assessment, limiting factors and opinions of importance. Informed consent was gained to include the responses in the study. The data was analyzed using descriptive statistics and Wilcoxon Signed Ranks Testing. The questionnaire was completed by 105 orthoptists. The methods reported to quantify ductions and fields of BSV respectively were: Goldmann (33% and 34%), Aimark (22 and 23%), Lister (7%), Octopus (5 and 4%), Thomson ocular motility analyzer (2 and 3%), Binocular vision analyzer (2%) and no method reported (30% and 32%). The frequency of measuring ductions and fields of BSV per week (median 1–2) was significantly less than the number of patients seen with limited ocular motility per week (median 6–9). The main reasons for never or rarely measuring ductions or fields of BSV were not enough time, no method available and only on selected patients. Respondents indicated that they would measure ductions and fields of BSV more frequently if a quicker portable method was available (median 3–5 times per week). Most agreed that measurements of ductions and fields of BSV are important (89 and 95% respectively). There is no standardized method of quantitively measuring ductions or fields of BSV, with almost a third of respondents not measuring either. Although most orthoptists agreed these measurements are important, they are infrequently performed. The main factors limiting these assessments are insufficient time and lack of a testing method. If a faster portable device was available, orthoptists would measure ductions and fields of BSV more frequently.